2007
DOI: 10.1002/glia.20468
|View full text |Cite
|
Sign up to set email alerts
|

Microglia derived from aging mice exhibit an altered inflammatory profile

Abstract: Microglia play a critical role in neurodegenerative diseases and in the brain aging process. Yet, little is known about the functional dynamics of microglia during aging. Thus, using young and aging transgenic mice expressing enhancedgreen fluorescent protein (EGFP) under the promoter of the c-fms gene for macrophage-colony stimulating factor receptor, we evaluated in vivo-induced inflammatory responses of EGFP-expressing microglia sorted by flow cytometry. Aging microglia were characterized by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
506
3
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 595 publications
(547 citation statements)
references
References 38 publications
34
506
3
4
Order By: Relevance
“…38 Many lines of evidence have shown that aged microglia may give rise to altered inflammatory profiles with increased production of pro-inflammatory factors. [39][40][41][42] In aged mice as compared with young mice, treatment with MPTP can cause severe DA neuron loss and greater microglial activation in the SN. 43 It is possible that aged microglia is undergoing phenotype transformation by epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…38 Many lines of evidence have shown that aged microglia may give rise to altered inflammatory profiles with increased production of pro-inflammatory factors. [39][40][41][42] In aged mice as compared with young mice, treatment with MPTP can cause severe DA neuron loss and greater microglial activation in the SN. 43 It is possible that aged microglia is undergoing phenotype transformation by epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that telomere shortening could alter immune response in the presence of an external stimulus without changing the basal cellular profile drastically. Previously, aged microglia have been shown to display enhanced pro‐inflammatory activity in response to LPS (Sierra et al ., 2007). I.p.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic inflammatory response, identified by increases in ED1 + activated microglia, has been demonstrated repeatedly in the CNS of young animals months after irradiation (8,10,13,14). To date, however, experimental studies of radiation-induced inflammation, brain injury and cognitive dysfunction have been conducted almost exclusively in animals a few weeks to a few months old, young ages that do not reflect important neurobiological changes that occur with normal aging, such as decreased proliferation and neurogenesis (15)(16)(17)(18), increased microglial activation (19,20) and expression of pro-inflammatory cytokines (20)(21)(22). Experimental studies of stroke, traumatic brain injury, exogenous cytokine administration, and axotomy support the hypothesis that aging impacts the intensity and duration of brain inflammation and glial activation following challenges (23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%